2011
DOI: 10.1186/1476-511x-10-73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n-3 PUFAs on breast cancer cells through their incorporation in plasma membrane

Abstract: BackgroundPUFAs are important molecules for membrane order and function; they can modify inflammation-inducible cytokines production, eicosanoid production, plasma triacylglycerol synthesis and gene expression. Recent studies suggest that n-3 PUFAs can be cancer chemopreventive, chemosuppressive and auxiliary agents for cancer therapy. N-3 PUFAs could alter cancer growth influencing cell replication, cell cycle, and cell death. The question that remains to be answered is how n-3 PUFAs can affect so many physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 43 publications
7
123
1
9
Order By: Relevance
“…after 72 hrs of treatment [20] and were able to incorporate fatty acids, to metabolize them and to insert them into cell membrane lipid rafts, as indicated by present data. The existence of elongases and desaturases able to metabolize PUFA is reported in many tumor cells [37].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…after 72 hrs of treatment [20] and were able to incorporate fatty acids, to metabolize them and to insert them into cell membrane lipid rafts, as indicated by present data. The existence of elongases and desaturases able to metabolize PUFA is reported in many tumor cells [37].…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly previous results from our lab [20] demonstrated that MCF-7 and MDA-MB231 cell membrane are rich of oleic acid with a very low saturation index around 0.5.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…20 An ELSD was used to detect and separate the phospholipid species. Cells were then collected using trypsin-EDTA, centrifuged and pellets were analyzed to evaluate protein content.…”
Section: Pc and Chol Dosagementioning
confidence: 99%
“…Paola et al [88] used MTT viability test and expression of apoptotic markers to evaluate the effect of PUFAs on cancer growth, and their results indicated that EPA and DHA might induce modifications of tumor cell membrane structure leading to an obviously decreased induction rate of breast cancer. Menéndez et al [89] also reported that omega-3 PUFAs ALA suppresses the overexpression of HER2, which plays an important role in aetiology, progression and chemosensitivity of various types of human cancers, suggesting that ALA is a potential anticancer agent.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%